Gauging the Impact of Clinical Computer Mediated Communication: Validation of a New Assessment Method - Grad, Roland; Pluye, Pierre; Mercer, Jay; Marlow, Bernard; Shulha, Michael; Johnson-Lafleur, Janique (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
A new impact assessment method facilitates knowledge transfer by promoting a two-way exchange between providers of health information and family doctors. Participants reported a high degree of conceptual use of email alerts. Interviews (research-in-progress) will document the meaning of all ten scale items in support of the content validity of the method. Une nouvelle méthode d’évaluation facilitant le transfert des connaissances préconise l’échange réciproque entre les fournisseurs d’information médicale et les médecins de famille. Les participants indiquent un haut degré d’utilisation conceptuelle des avis reçus par courriel. Des entrevues (en cours de réalisation) fourniront des renseignements sur les dix facteurs sur lesquels est basée la validité de contenu de cette méthode.